2016
DOI: 10.1080/01913123.2016.1234530
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in epithelial cells of rats exposed to low concentration of hydrogen sulfide for 50 days

Abstract: Hydrogen sulfide (HS) and other volatile sulfur compounds (VSCs) appear mainly in the oral air of patients with halitosis. It seems that VSCs are directly involved in the pathogenesis of gingival diseases. In previous studies, short-term (7 hours-4 days), high concentrations (5-400 ppm) of HS applications on periodontal tissues have been evaluated in a culture medium. The aim of the present study was to investigate the potential effects of lower (equivalent to halitosis) concentrations of HS on rat gingival ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The H 2 S is a known genotoxic agent, which has an impact on genomic instability and cumulative mutations [68]. In studies on rats, it was demonstrated that hydrogen sulfide leads to ultrastructural changes in epithelial cells and periodontal destruction [69]. Increased amounts of H 2 S by the activation of proliferation, migration, and invasion can also lead to carcinogenesis [70,71].…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…The H 2 S is a known genotoxic agent, which has an impact on genomic instability and cumulative mutations [68]. In studies on rats, it was demonstrated that hydrogen sulfide leads to ultrastructural changes in epithelial cells and periodontal destruction [69]. Increased amounts of H 2 S by the activation of proliferation, migration, and invasion can also lead to carcinogenesis [70,71].…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…Intraoral halitosis is caused by several factors including oral bacteria and diseases [ 77 ]. Mimicking intraoral halitosis by treating rat epithelial cells with low concentrations of H 2 S gas for 50 days results in significant changes in cellular structure, vacuolization, and loss of intercellular matrix resembling halitosis in human [ 78 ]. An increase in the abundance of H 2 S-producing oral bacteria in oral biofilm has been associated with the disease [ 79 ].…”
Section: H 2 S and Oral Diseasesmentioning
confidence: 99%
“…VSCs can cause the damage to fibroblasts, resulting in periodontal disease (Chen et al, 2010; Yaegaki et al, 2008). At the same time, VSCs can be transported to various organs of the body through blood, influencing the normal function and metabolic activity of tissues and organs (Hu et al, 2014; Yalcin Yeler et al, 2016). Therefore, the excessive production of VSCs not only affects the social interaction of patients but also harms oral and systemic health.…”
Section: Introductionmentioning
confidence: 99%
“…blood, influencing the normal function and metabolic activity of tissues and organs (Hu et al, 2014;Yalcin Yeler et al, 2016). Therefore, the excessive production of VSCs not only affects the social interaction of patients but also harms oral and systemic health.…”
mentioning
confidence: 99%